Improved method for assessing iron stores in the bone marrow. Issue 8 (28th July 2009) - Phiri, K S; Calis, J C J; Kachala, D; Borgstein, E; Waluza, J; Bates, I; Brabin, B; van Hensbroek, M Boele
Abstract : Background: Bone marrow iron microscopy has been the "gold standard" method of assessing iron deficiency. However, the commonly used method of grading marrow iron remains highly subjective. Aim: To improve the bone marrow grading method by developing a detailed protocol that assesses iron in fragments, in macrophages around fragments and in erythroblasts. Methods: A descriptive study of marrow aspirates of 303 children (aged 6–60 months) with severe anaemia and 22 controls (children undergoing elective surgery) was conducted at hospitals in southern Malawi (2002–04). Results: Using an intensive marrow iron grading method, 22% and 39% of cases and controls had deficient iron stores, and 40% and 46% had functional iron deficiency, respectively. Further evaluation of the iron status classification by the intensive method showed that functional iron deficiency was associated with significantly increased C-reactive protein concentrations (126.7 (85.6) mg/l), and iron stores deficiency with significantly increased soluble transferrin receptor concentrations (21.7 (12.5) μg/ml). Conclusions: Iron assessment can be greatly improved by a more intense marrow examination. This provides a useful iron status classification which is of particular importance in areas where there is a high rate of inflammatory conditions.